PHYSICS LEARNING CHAPTER E-BOOK DESIGN ORIENTED BY CRITICAL AND CREATIVE THINKING ABILITY USING A CASE-BASED REASONING APPROACH TO MEASURING MATERIALS - Nurfadiah, Dinda (Universitas Negeri Padang, 2024)
The limited critical and creative thinking abilities observed in students within the field may be attributed to various factors, such as suboptimal learning approaches and the absence of critical and creative thinking skills in teaching materials. An initiative to enhance these skills involves the creation of an e-book chapter focused on physics learning, emphasizing critical and creative thinking and employing an appropriate approach. This research endeavors to formulate an e-book chapter centered on critical and creative thinking skills, utilizing a valid and practical case reasoning approach. The study is conducted as part of Research and Development (R&D), employing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Validation of the e-book chapter is undertaken with input from three physics lecturers at UNP. Practicality testing involves six physics teachers from Padang 3 Public High School, Padang 5 Public High School, and Padang 16 Public High School, as well as students from Padang 16 Public High School. The outcomes of the practicality test indicate that the e-book falls within the highly practical category, garnering assessments of 94.9% and 88.34% from teachers and students, respectively